Hybridité des formes d`engagement sociétal et financement public. L`exemple du football professionnel français - Boucher, W.; François, A.; Dermit-Richard, N. (Movement & Sport Sciences - Science & Motricité, 2021)
In recent years, there has been a growing phenomenon in France of the creation of associations, endowments and/or foundations by professional sports clubs wishing to carry their social commitment through these structures. This article aims to find out whether this phenomenon reflects a transformation in the way clubs are involved. We have chosen football as the field of investigation by selecting all clubs in Ligue 1 having created at least one of these structures in 2018-2019. Through interviews with operational managers and secondary data, we show the process of hybridization of the commitment at work characterized by common governance, resources and actions between clubs and dedicated structures. While these new hybrid forms of commitment allow for better operationalization, our results also show that its evaluation remains very sketchy. Although made complex by the hybridity observed, the evaluation of societal commitment nevertheless appears essential to justify its effectiveness and thus, from the point of view of public management, to legitimize the direct and/or indirect public aid paid jointly to these structures and the clubs that created them.